Construction and Validation of a Chloroplast Expression Vector for the Production of Recombinant Proteins in Chlorella vulgaris - Bolaños-Martínez, Omayra C.; Malla, Ashwini; Rosales-Mendoza, Sergio; Vimolmangkang, Sornkanok (Frontiers in Marine Science, 2022)
Microalgae constitute a diverse group of photosynthetic unicellular microorganisms that have gained immense attention for biotechnological applications. They are promising platforms for the production of high-value metabolites and biopharmaceuticals for commercial and therapeutic applications because of their physiological properties and capability to grow easily in natural and artificial environments. Although the proof-of-concept for some applications have been achieved for model species, such as Chlamydomonas reinhardtii, the genetic engineering methods for microalgae are still in their infancy. Thus, an expansion of this field is required. Chlorella vulgaris is an important algal species with a high protein content and requires focus for the development of an efficient nuclear and chloroplast transformation process. This research aimed to establish a chloroplast transformation method for the freshwater green-algae species C. vulgaris based on a specific expression vector (pCMCC, which was named after Chula Mexico Chlorella chloroplast) constructed with endogenous recombination regions, namely, 16S–trn I (left) and trn A–23S (right), and the Prrn promoter. Human basic fibroblast growth factor (bFGF) was adopted as a target biopharmaceutical to establish the chloroplast expression approach. The plasmid pCMCC:bFGF was transformed into C. vulgaris via electroporation using simple carbohydrate-based buffers, which aided in the transfer of the transgene into the chloroplast genome. Cells transformed with the pCMCC:bFGF vector were selected using kanamycin, and resistant colonies were analyzed by polymerase chain reaction and Western blotting to confirm the presence of the transgene and the recombinant bFGF, respectively. The bFGF that accumulated in the transplastomic C. vulgaris clones ranged from 0.26 to 1.42 ng/g fresh weight of biomass, and it was quantified by enzyme-linked immunosorbent assay. Therefore, the designed expression vector, in combination with an optimized electroporation protocol, constitutes a viable approach to successfully develop transplastomic lines of C. vulgaris for the potential low-cost production of biopharmaceuticals using this algal species. This study paves the way for the establishment of chloroplast biotechnology in microalgae other than the model organism C. reinhardtii.